2012
DOI: 10.1021/ic300826p
|View full text |Cite
|
Sign up to set email alerts
|

Building-up Remarkably Stable Magnesium Porphyrin Polymers Self-Assembled via Bidentate Axial Ligands: Synthesis, Structure, Surface Morphology, and Effect of Bridging Ligands

Abstract: A series of supramolecular architectures of magnesium tetranitrooctaethylporphyrins mediated by several bidentate axial ligands have been synthesized in excellent yields and structurally characterized. Six conjugated axial ligand with increasing chain lengths have been utilized in the present investigations in which the Mg···Mg nonbonding distance between successive ions also increases from 0.73 to 2.70 nm in the series. To the best of our knowledge, this is the first report where stable metallo-porphyrin poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 88 publications
(45 reference statements)
4
19
0
Order By: Relevance
“…general. This is in line with findings for gradually elongated porphyrin systems [8,9]. The most efficient solvent inclusion has been found for a biphenyl spacer showing an inclusion ratio comparable to previously discussed molecules having phenyl or an ethynlene spacer.…”
Section: Solvent Vapor Absorption Behaviorsupporting
confidence: 91%
See 2 more Smart Citations
“…general. This is in line with findings for gradually elongated porphyrin systems [8,9]. The most efficient solvent inclusion has been found for a biphenyl spacer showing an inclusion ratio comparable to previously discussed molecules having phenyl or an ethynlene spacer.…”
Section: Solvent Vapor Absorption Behaviorsupporting
confidence: 91%
“…Hence, it is convincingly shown that the covalently linked axis of a conventional wheeland-axle host molecule can be replaced by a system of hydrogen bonds or by coordination of ligands generating inclusions alike. Moreover, derived from the existing findings, the length of the central axis is demonstrated to decisively control the void dimensions as well as the mode of aggregation in the crystal including, e.g., wheel-and-axle or shish-kebab type shapes of supramolecular scaffolds [8,9], aside from the kind of subunits that compose the molecular wheels exercising a similar effect. Only recently, steroidal wheel-and-axle-type hosts [11] as well as the exchange of the lateral aryl groups of respective host molecules against heterocycles [12] opened up a further new way of structural modification, showing high potential to control inclusion selectivity of organic guest species.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The polymers form linear structures with porphyrin units perpendicular to the ligands, but with increasing length of the axial ligands, some porphyrin units also fill the spaces by aligning parallel to the ligands. 57 Cao et al published two papers in 2013 concerning selfassembly of side-chain-coordinated Zn and Hg porphyrin MOFs studied for solar photovoltaic cells (Fig. 22).…”
Section: Coordination Polymersmentioning
confidence: 99%
“…Axial complexation of pyridyl moieties to metalloporphyrin centers can lead to supramolecular assemblies such as cages [5], oligomers [6], polymers [7], wires [8], or tweezers [9]. Complementing the intriguing properties of porphyrins are those of polycyclic aromatic hydrocarbons such as pentacenes.…”
Section: Introductionmentioning
confidence: 99%